Approaches to landmarks in Costa Rican addresses - Bolaños Carpio, Alexa (2021)
This article examines the relationship of landmarks and people’s identity as landmarks are objects of material culture. This is a qualitative research based on grounded theory and material culture. The corpus consists of 129 telephone calls to the 9-1-1 Emergency System in Costa Rica. Findings show that bridges, entrances, churches and schools are the most used landmarks. First, bridges and entrances are landmarks due to their prominence and frequency of use, since they serve as means of communication and show their daily and vital relationship with people. Second, churches and schools are landmarks due to their cultural significance and frequency of encounter, as both objects have deep roots in Costa Rica. Schools evidence the need to make the people literate, and an equalizing mechanism of society that functions as a subjective element of national identity, whereas the churches evidence a subjective element of the national identity and the Catholic tradition of the country. Finally, landmarks show identity’s aspects of the people, as they allow us to trace some historical interactional changes that the communities experience.